1997
DOI: 10.3109/08820139709022692
|View full text |Cite
|
Sign up to set email alerts
|

An RGD Containing peptide from HIV-1 TAT-(65–80) modulates protooncogene expression in human bronchoalveolar carcinoma cell line, A549

Abstract: Tat (transactivator of transcription) is essential for HIV-1 replication in vivo and in vitro. Tat-(65-80), an RGD containing domain, has been shown to regulate proliferative function of a variety of cell lines, including a human adenocarcinoma cell line, A549. The exact cellular and molecular mechanisms by which these effects are mediated, remain unknown. To evaluate the hypothesis that Tat-(65-80) modulates the expression of immediate early genes (IEG) c-jun, c-myc, c-fos and the tumor suppressor gene p53, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(2 reference statements)
2
19
1
1
Order By: Relevance
“…30 -33 Some in vitro studies have shown that the HIV tat gene may modulate the expression of certain protooncogenes (c-myc, c-fos, and p53) in malignant cells. 34 The role of HIV itself in the development of solid malignancies, if it exists, probably is relatively minor compared with the impact of risk factors such as tobacco use, alcohol use, poor nutrition, coinfection with other protooncongene viruses (e.g., hepatitis, human papillomavirus, etc. ), and immunodepression, which often is present in HIV-infected patients and should be the target of preventive and curative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…30 -33 Some in vitro studies have shown that the HIV tat gene may modulate the expression of certain protooncogenes (c-myc, c-fos, and p53) in malignant cells. 34 The role of HIV itself in the development of solid malignancies, if it exists, probably is relatively minor compared with the impact of risk factors such as tobacco use, alcohol use, poor nutrition, coinfection with other protooncongene viruses (e.g., hepatitis, human papillomavirus, etc. ), and immunodepression, which often is present in HIV-infected patients and should be the target of preventive and curative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…HIV itself might have a direct oncogenic role. Although limited experimental data suggest that the HIV tat gene product may modulate expression of growth-related genes, amplification of HIV sequences in lung carcinoma tissue has not been demonstrated (55,56). Further, the limited data on risk for lung cancer associated with HIV RNA levels has not been suggestive of a strong association (4,36,41).…”
Section: Role Of Immunosuppression Hiv Viral Load and Artmentioning
confidence: 99%
“…Tat-(65-80), an RGD-containing domain, has been shown to regulate the proliferative functions of a variety of cell lines, including a human adenocarcinoma cell line, A549. Treatment with Tat-(65-80) has been shown to reduce the p53 gene product fivefold, whereas c-fos gene transcription increased sevenfold at 0.5 h posttreatment and subsequently declined to baseline levels at 8 h. Therefore, it was suggested that Tat-(65-80) can modulate growth-related genes in cells (12). A similar result has also been reported in which Tat inhibits the transcription of p53, and the downregulation of p53 by Tat may be involved in the development of AIDS-related malignancies (26).…”
mentioning
confidence: 99%